Determination of bovine rotavirus genotypes (G and P) circulating in Uttarakhand (2010-2012) by polymerase chain reaction - MALIK, YASHPAL SINGH; SHARMA, KULDEEP; KUMAR, NAVEEN; HAQ, ADIL A; VAID, NIRUPMA (The Indian Journal of Animal Sciences, 2014)
The study describes the prevailing bovine rotavirus (RV) genotypes in high altitude areas of Uttarakhand state of India. The results confirmed the dominance of G3 genotype, which is responsible for diarrhea either alone or together with G8 and G10 genotypes. The P typing results on the other hand showed prevalence of only P[11] genotype in all bovine rotavirus isolates, confirming that least diversity exists in the major outer capsid protein gene (VP4) of bovines. The rotavirus existed in 4 types of genotypic combinations i.e. G3P[11], G10P[11], G3G8P[11] and G3G10P[11] in cattle calves of the region.